DAMPAK TEKNOLOGI TERHADAP MARAKNYA PLAGIARISME DIKALANGAN MAHASISWA : Studi Kasus di UIN Syekh Wasil Kediri - Anis Humaidi; Najihatul Fadhliyah; Dina Ameliana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This paper will discuss the prevalence of plagiarism, why plagiarism occurs, the forms of plagiarism, and measures to combat plagiarism among students at UIN Syekh Wasil Kediri. The research method chosen is qualitative descriptive, which aims to provide a systematic, factual, and accurate description or portrayal of the facts regarding the phenomenon under investigation. The research data was sourced from faculty members and students. This study employed three data collection techniques: observation, interviews, and documentation. The data analysis used in this study is based on the framework developed by Miles and Huberman. The findings of this study indicate that the rate of plagiarism among students is relatively high. The causes include the availability of technology that makes it easier for students to commit plagiarism, a lack of understanding of how to write a paper, the absence of specific courses or training on academic writing, a lack of attention from instructors regarding plagiarism, and an excessive workload. The forms of plagiarism committed by students at UIN Syekh Wasil Kediri include copying and pasting then changing the author’s name, copying and pasting then paraphrasing, and copying and pasting then paraphrasing using Perplexity and ChatGPT. Efforts to combat plagiarism among students at UIN Syekh Wasil Kediri have been undertaken by faculty members, but they have not been fully effective, as many faculty members still lack awareness of the plagiarism issue. For those faculty members who are aware of the issue, they educate students on the dangers and negative consequences of plagiarism, check the originality of student work using Turnitin, and provide solutions for students who lack academic skills.